Simulation and gamification as educational tools for the diagnosis of molar-incisor hypomineralization - Caracho, Rafaela Aparecida (2025)
Molar-Incisor Hypomineralization (MIH) has gained attention in the scientific literature and clinical environment due to its prevalence, impact on the quality of life of the patient and their family, and especially its diagnostic and treatment challenges. The objective of this study was to compare and evaluate the use of two strategies against conventional teaching, as well as to compare two indices in assessing the improvement of diagnostic capability for MIH among undergraduate students. The study was conducted at the Bauru School of Dentistry, involving two separate fourthyear undergraduate classes from different years. Simulation-based teaching was evaluated in one class, and in the other class, gamification was used. Both teaching methods were compared to conventional teaching. The methodology used was similar in both investigations, with two study groups: the conventional method group (only theoretical class) and the simulation or gamification group. Initially, a theoretical class on MIH was taught to both groups, after which the conventional group underwent diagnostic evaluation, while the other group participated in a practical activity involving active methodologies (simulation or gamification). Following that, they underwent a diagnostic evaluation similar to the conventional group, using photographs where students had to provide a diagnosis using the HMI and MIH-SSS indices. The students also filled out a questionnaire to assess their perception of the activity and their preferences regarding the indices used. The outcome analyzed was the number of correct answers. Statistical analysis was performed using two-way Analysis of Variance, considering the type of index and teaching method. The results revealed that for both studies, diagnostic capability was greater in groups where active teaching methodologies were applied and when the EAPD index was used. Overall, student perception was more positive when active methodologies were applied, and there was no preference for one index over the other.